Pembelajaran Tari di SMAN 1 Tambang dengan Menggunakan Projek Based Learning - Dilla Oktavia; Idawati Idawati (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This research aims to determine dance learning at SMA Negeri 1 Tambang using Project Based Learning. The theory used in this research is Sani's theory (2014: 180) regarding the implementation of Project Based Learning in Dance Learning. This research uses a descriptive analysis method using qualitative data because the researcher did not carry out processing or testing, through in-depth study using data collection techniques directly from people in his scientific circle. The data collection techniques used are observation, interviews, documentation. Based on the research results, it can be concluded that dance learning at SMA Negeri 1 Tambang using Project Based Learning can be carried out well. This is proven from the research results that the teaching process carried out by the teacher is in accordance with the teaching steps themselves, namely by starting projects, building knowledge, development and exposure of dance learning products/projects.